Operating procedures for electrochemotherapy in bone metastases: Results from a multicenter prospective study on 102 patients. Issue 10 (October 2021) - Campanacci, Laura; Bianchi, Giuseppe; Cevolani, Luca; Errani, Costantino; Ciani, Giovanni; Facchini, Giancarlo; Spinnato, Paolo; Tognù, Andrea; Massari, Leo; Cornelis, Francois H.; Mosconi, Mario; Screpis, Daniele; et al.
Abstract: Introduction: Bone metastases are frequent in patients with cancer. Electrochemotherapy (ECT) is a minimally invasive treatment. Preclinical and clinical studies supported the use of ECT in patients with metastatic bone disease (MBD). The purposes of this multicentre study are to confirm the safety and efficacy of ECT, and to identify appropriate operating procedures in different MBD conditions. Materials and methods: 102 patients were treated in 11 Centres and recorded in the REINBONE registry (a shared database protected by security passwords): clinical and radiological information, ECT session, adverse events, response, quality of life indicators and duration of follow-up were registered. Results: 105 ECT sessions were performed (one ECT session in 99 patients, two ECT sessions in 3 patients). 24 patients (23.5%) received a programmed intramedullary nail after ECT, during the same surgical procedure. Mean follow-up was 5.9 ± 5.1 months (range 1.5–52). The response to treatment by RECIST criteria was 40.4% objective responses, 50.6% stable disease and 9% progressive disease. According to PERCIST criteria the response was: 31.4% OR; 51.7% SD, 16.9% PD with no significant differences between the 2 criteria. Diagnosis of breast cancer and ECOG values 0–1 were significantly associated to objective response. A significant decrease in pain intensity and significant better quality of life was observed after ECT session at follow-up. Conclusion: The results are encouraging on pain and tumour local control. ECT proved to be an effective and safe treatment for MBD and it should be considered as an alternative treatment as well as in combination with radiation therapy.